Collaborative Governance in the Elderly Population Empowerment Program in Penggilingan Village, East Jakarta Administrative City - Deddy Rachman; Amy Yayuk Sri Rahayu (Publikasi Indonesia, 2024)
Indonesia is undergoing a demographic shift towards an aging population, with an increasing number of elderly citizens. This research aims to analyze the implementation of collaborative governance in the empowerment of elderly residents in Penggilingan, East Jakarta. The study employs a qualitative descriptive approach with case study methods, focusing on the involvement of various stakeholders such as local governments, NGOs, and community groups. Data were collected through interviews, observations, and document analysis. The results indicate that collaborative governance has been implemented through regular forums, promoting communication and coordination among stakeholders. However, challenges such as limited resources and insufficient trained personnel hinder optimal program outcomes. The findings highlight key factors influencing the success of collaborative governance, including leadership, mutual trust, shared vision, and community participation. Strengthening stakeholder capacity and increasing resource allocation are recommended for improving the program's effectiveness. Further research is suggested to explore innovative models of collaborative governance for elderly empowerment in Indonesia.